Glycated Albumin Percentage is Correlated With HbA1c : Theoretic Marker in Patients With Altered Erythrocyte Turnover - Gåfvels, Mats; Swärd, Per; Xu, Ning; Svensson, Joel (Journal of diabetes science and technology, 2025)
INTRODUCTION: The gold standard for monitoring long-term glucose levels in patients with diabetes mellitus is glycated hemoglobin (HbA1c). In conditions where the erythrocyte half-life is decreased, for example, in long-term kidney diseases and hemoglobinopathies, HbA1C may underestimate the long-term glucose exposure. Therefore, in these patient groups, other methods to monitor long-term glucose have been suggested, including glycated serum protein (GSP). To further optimize the method, a correction against total serum albumin has been proposed, defined as a percentage of glycated albumin (%GA). The aim of this study was to investigate the correlation between HbA1c, GSP, and %GA-a strong correlation to HbA1c would strengthen the potential usefulness of GSP and %GA as alternative methods to monitor glucose exposure in certain patient populations. METHODS: In this study, randomly collected human samples (n = 271), with different levels of HbA1c were analyzed for GSP and total serum albumin and a %GA was calculated. We also divided the samples into subgroups based on their HbA1c-result, age, and gender. RESULTS: Both %GA and GSP were strongly correlated with HbA1c, where %GA displayed the strongest correlation (R2 0.77 compared with R2 0.66.). When dividing into subgroups based on HbA1c-results, statistically significant differences in %GA were observed between all the different subgroups. CONCLUSION: In conclusion, the findings of this study strengthen the possibility of using GSP and %GA as possible alternatives or at least a supplement to HbA1c for monitoring long-term glucose exposure. Theoretically, particularly %GA could have the potential to supplement HbA1C in patients where the erythrocyte half-life is altered.